2001
DOI: 10.1017/s0004972700039939
|View full text |Cite
|
Sign up to set email alerts
|

A note on the ideals of groupoid C*-algebras from Smale spaces

Abstract: In this note, we characterise completely the ideals of the groupoid C* -algebra arising from the asymptotic equivalence relation on the points of a Smale space and show that the related Ruelle algebra is simple when the Smale space is topologically transitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Hence if log(λ) is the entropy then λ > 1. (2) The homoclinic algebra of a mixing Smale space has a unique tracial state τ H , see [16] and Subsection 2.5 above.…”
Section: Real Rank Zeromentioning
confidence: 99%
“…Hence if log(λ) is the entropy then λ > 1. (2) The homoclinic algebra of a mixing Smale space has a unique tracial state τ H , see [16] and Subsection 2.5 above.…”
Section: Real Rank Zeromentioning
confidence: 99%
“…The traces on C * (S) and C * (U ) are not bounded while C * (H) admits a tracial state. Moreover, when (X, ϕ) is mixing, this trace is unique [25].…”
Section: Definitionmentioning
confidence: 99%
“…Abstract and Applied Analysis 3 Then, is a second countable, locally compact, Hausdorff,discrete, and principal groupoid under this topology, and the counting measure is a Haar system [2,7,8]. The path space Λ Δ is identified with the unit space 0 by the embedding map → ( , ).…”
Section: 2mentioning
confidence: 99%
“…For an irreducible Smale space ( , ), Putnam and Spielberg [3] showed that groupoids defined by stable and unstable equivalence relations are essentially principal, and Hou and Chen [7] showed that ⋊ Z is essentially principal. Recall that a Smale space is said to be irreducible if it is nonwandering and has a dense orbit.…”
Section: Propositionmentioning
confidence: 99%
See 1 more Smart Citation